Frequency of Hearing Impairment among Full-term Newborns in Yazd, Iran - Islami, Zia (Tehran University of Medical Sciences, 2013)
OBJECTIVE: Permanent congenital hearing loss, a common congenital anomaly, may affect speech and language acquisition, academic achievement and social development. Current standards emphasize early recognition of congenital hearing loss. This study was conducted to find the prevalence of hearing impairment in term newborns in Yazd, Iran. METHODS: This was a descriptive-analytic study conducted in Yazd on 7250 term newborns. Otoacoustic emissions (OAEs) test was performed in all newborns during the first 24 hours after birth. Those who failed to respond at the first step were retested 15 days later. Those who failed to respond at the second step too, were tested by acoustic brainstem responses (ABR) test. Chi square test was used for data analysis. FINDINGS: From 7250 newborns in the first step 598 (8.2%) and 682 (9.4%) ears (right and left, respectively) failed. In the second step 51 (0.7%) and 58 (0.8%) ears (right and left, respectively) failed. Consanguinity and route of delivery had significant effect on the frequency of hearing loss. CONCLUSION: The overall frequency of congenital hearing loss in this study was found high.